(untitled) (Studia theodisca, 2018)
This study explores Karl Kraus’ case against ministerial incentives to promote tourism. Kraus covers the overlap between tourism and war propaganda, treating an apparently insignificant cultural phenomenon as a symptom of collective spiritual decay. As Kraus sees it, the governmental push to cultivate tourism serves as a diversion for Austrians amid the economic uncertainty brought on by the Great War. This essay examines instances of the theme in the Buchausgabe (1926) of the drama Die Letzten Tage der Menschheit, together with a selection of articles and glosses from Die Fackel (1899-1936).